Update on Critical Issues on Infant and Neonatal Care - Mauricio Barría, René (IntechOpen, 2020)
Infant and neonatal health is one of the areas of greatest development and evolution within pediatrics. This edited volume Update on Critical Issues in Infant and Neonatal Care is a collection of reviewed and relevant research chapters offering a comprehensive overview of recent developments in six topics about common newborn and infant health problems. In 6 chapters that address relevant issues about infant and neonatal care, the book seeks to contribute to the clinical work of the health teams of critical care units. Specialists in the field of pediatrics from different countries have developed these chapters and through them they hope to share part of their experience.